HUBUNGAN ANTARA USIA, SHIFT KERJA, BEBAN KERJA, STRES KERJA, KONSUMSI KAFEIN DAN KEBIASAAN OLAHRAGA DENGAN INSOMNIA - Anggeriani, Desy; Trisnawati, Elly; Rossa, Idjeriah (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2016)
Insomnia is difficulty to sleep that makes people feel not enough sleep when awakened caused by one or multifactorial. Nurses who work with shift mechanism will experience a disruption of circadian rhythms. Stressor-stressor in the work environment also have an impact on irregular sleep patterns and lifestyles such as caffeine and lack of exercise. Insomnia can affect a decrease in workers work performance, productivity and quality of work, relationships at work, decreased alertness, disruptions in family life and increases the risk of accidents. The purpose of this study was to investigate the relationship between age, shift work, workload, work stress, caffeine, and exercise habits with insomnia in nurses.This study uses a cross-sectional design. The location of research in hospitals DR.Soedarso Pontianak. Samples are 66 respondents taken by simple random sampling technique. Using the Chi-Square test with a confidence level of 95%. The results showed a significant relationship between shift work (p value = 0.014; PR = 2.74, 95% CI = 1.01 to 7.42), caffeine (p value = 0.000; PR = 6.23, 95 % CI = 2.51 to 15.46), exercise habits (p value = 0.048; PR = 1.615, 95% CI = 1.01 to 2.57) with insomnia in nurses. Variables that are not associated with insomnia in nurses are age (p value = 0.292; PR = 0.39, 95% CI = 0.07 to 2.19), workload (p value = 0.387; PR = 0.80, 95 % CI = 0.54 to 1.18), job stress (p value = 0.374; PR = 1.30, 95% CI = 0.80 to 2.12). It is suggested to hospital management to implement policies optimal for each nurse to not change the shift schedule that has been set to avoid the occurrence of work shifts sequentially mainly shift night work, reduce the amount of consumption of caffeinated beverages and regularly exercise at least 3 times a week with a duration of 30 minutes - 1 hour per day.Key words: shift work, caffein, sports, insomnia, nurse.